Effects of distant metastasis and peripheral CA 15-3 on the induction of spontaneous T cell responses in breast cancer patients - Domschke, Christoph; Schütz, Florian; Sommerfeldt, Nora; Rom, Joachim; Scharf, Alexander; Sohn, Christof; Schneeweiss, Andreas; Beckhove, Philipp (Cancer immunology immunotherapy, 2010)
Tumor-specific memory T cells are detectable in the bone marrow (BM) of a majority of breast cancer patients. In vitro they can be reactivated to IFN-γ producing, cytotoxic effector cells and reject autologous, xenotransplanted tumors in NOD/SCID mice after specific restimulation with autologous dendritic cells (DC). In this study, we demonstrate the presence of specific tumor-reactive BM memory T cells in altogether 56 out of 129 primarily operated breast cancer patients by short-term IFN-γ EliSpot assays with unstimulated T cells and tumor antigen presenting, autologous DCs. We observed tumor-reactive BM memory T cells predominantly in patients with primarily metastatic disease (P = 0.011) or with increased concentrations of tumor marker CA 15-3 in the peripheral blood (P = 0.004), respectively. Memory T cell reactivity against HLA-A*0201-restricted peptides from the tumor-associated antigens MUC1, Hpa16-24 and Hpa183-191 was also detected particularly in patients with elevated peripheral CA 15-3 concentrations (P < 0.05). Altogether these data indicate that the systemic presence of tumor-derived antigens promotes an induction of tumor-specific cellular immune responses in the human BM.
Published online: 2 December 2009
Gesehen am 16.02.2023